The Method of CT Dosimetry Based on the CTDI (Computed Tomography Dose Index) for the Treatment of the Human's Head - Rini Safitri; Nurmalita . (PSI-Aceh, 2014)
The method of CT dosimetry based on the CTDI is a common measurement method by using a single, axial rotation about a pencil chamber in a stationary phantom. For some time now there has been a growing awareness that radiation dose originating from medical diagnostic procedures in radiology, is contributing an increasing proportion to the total population dose, with a large component coming from CT examinations. This is accompanied by rapid developments in CT technology, including the use of increasingly wide X ray scanning beams, which are presenting problems in dosimetry that currently cannot be adequately addressed by existing standards. When preparing any dosimetric assessment of a CT scanner it is essential to have a good knowledge of the production of X rays and the characteristics of the CT scanner. Factors that influence the X ray beam intensity and photon spectrum are the tube voltage, the anode material, and anode angle, the filtration of the X ray tube, and the tube current. The properties of the radiation field for CT dose considerations can be characterized by free in air measurements of air kerma (absorbed dose in air). Measurements in standard cylindrical phantoms yield dosimetric quantities such as CTDI that can be considered as a patient dose index, and are also useful for quality assurance purposes, however they should not be interpreted as patient dose.